Indústria cultural e gratuidade na midiatização do campo evangélico - Hoerlle, Elisa (Universidade do Vale do Rio dos Sinos, 2013)
The object of this research is the tension between the market phenomenon, that moves production and consumption of materialities in the evangelical culture, and its religious references. We question in what ways can we understand the emergency of an evangelical cultural industry as a phenomenon of midiatized religion, and which distinct functions are performed by its products in the religious field. Our work hypothesis manifests a spiritual tension, product of the insertion of a religious group in the world of objects. Theoretically, we mobilize propositions about midiatization and cultural industry. In this situation, the scoop will be to verify manifestations of kenotic deflation and of the sublimation and desublimation dialetics in the sphere of religious culture. The research methodology takes an effort to overcome the views about the domination by technique. The corpus gathers very diverse products, organized in categories that reveal specific actions. Considering the midiatization processes in society, we perceive the empowerment of the gospel movement in relation to its original religious field. The evangelical cultural production covers operations from distinct institutions; religious, economical, artistic. It is, nevertheless, organized by the gospel culture, that centralizes all its dispositions. One of them, in particular, is pretty simple, and guarantees the circularity contact among the actors in the industry: evangelicals create for evangelicals. Our research delineates an undetermined social situation, fruitful for making inferences over the context change of the institutions by the midiatization processes in society. We see this transformation by the coping of the religious with the mediatic field, historical competitors in the role of general world explanation.
Keywords: Cultura gospel; Indústria cultural; Religião midiatizada; Gratuidade; Heterogeneidade; Sublimação; Dessublimação; Gospel culture; Cultural industry; Midiatized religion; Gratuity; Heterogeneity; Sublimation; Dessublimation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação